2019
DOI: 10.1091/mbc.e19-04-0209
|View full text |Cite
|
Sign up to set email alerts
|

TheDrosophilaAfadin and ZO-1 homologues Canoe and Polychaetoid act in parallel to maintain epithelial integrity when challenged by adherens junction remodeling

Abstract: During morphogenesis, cells must change shape and move without disrupting tissue integrity. This requires cell–cell junctions to allow dynamic remodeling while resisting forces generated by the actomyosin cytoskeleton. Multiple proteins play roles in junctional–cytoskeletal linkage, but the mechanisms by which they act remain unclear. Drosophila Canoe maintains adherens junction–cytoskeletal linkage during gastrulation. Canoe’s mammalian homologue Afadin plays similar roles in cultured cells, working in parall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(105 citation statements)
references
References 95 publications
13
92
0
Order By: Relevance
“…The studies in Drosophila showed that canoe regulates the maintenance of AJs in some morphogenetically active cells, but not in steady-state cells ( Sawyer et al, 2009 ). In addition, recent studies revealed that afadin or canoe plays critical roles for the dynamic regulation of AJs ( Choi et al, 2016 ; Manning et al, 2019 ). Therefore, afadin may play especially important roles in the maintenance of AJs and the proper actomyosin organization at AJs where the cell dynamics and force in tissue are elevated.…”
Section: Discussionmentioning
confidence: 99%
“…The studies in Drosophila showed that canoe regulates the maintenance of AJs in some morphogenetically active cells, but not in steady-state cells ( Sawyer et al, 2009 ). In addition, recent studies revealed that afadin or canoe plays critical roles for the dynamic regulation of AJs ( Choi et al, 2016 ; Manning et al, 2019 ). Therefore, afadin may play especially important roles in the maintenance of AJs and the proper actomyosin organization at AJs where the cell dynamics and force in tissue are elevated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the leading edge of the epidermis during Drosophila dorsal closure has a repeated pattern of myosin 2 localization that resembles "bars-on-a-string," with each bar representing a single leading edge cell (Franke et al 2005). Recent super-resolution microscopy of leading edge cells has shown that Ena-a protein that promotes F-actin plus end elongation-localizes to the adherens junctions, suggesting that F-actin plus ends are enriched facing outwards from a central myosin 2 bar (Manning et al 2019). Given that leading edge cells have centrally localized myosin 2 and peripherally enriched F-actin plus ends, this topology again resembles a sarcomere.…”
Section: Spatial Organizationmentioning
confidence: 99%
“…Similarly to previous work 26 , we also find no bias towards cell divisions orientated in the plane of the epithelium, suggesting that, at these early stages of Our results highlight the previously underappreciated localisation of ASPP2 at tricellular junctions in epithelial cells, in particular of the epiblast, and reveal the unknown biological function of ASPP2/PP1 complexes in the regulation of F-actin organisation at the apical junction. Considering that Afadin regulates the architecture of tricellular junctions in response to tensions 31,47 , the interaction between Afadin and ASPP2 strongly suggests that ASPP2 may exert its F-actin function at tricellular junctions via Afadin. The role of Afadin in regulating the linkage between F-actin and junctions during apical constrictions 48 suggests that ASPP2 may also be important in this process, which may be particularly relevant in the primitive streak.…”
Section: Discussionmentioning
confidence: 99%